Prevalence of urogenital and intestinal schistosomiasis among school children in South-west Nigeria. - Johnson A Ojo; Samuel A Adedokun; Akeem A Akindele; Adedolapo B Olorunfemi; Olawumi A Otutu; Taiwo A Ojurongbe; Bolaji N Thomas; Thirumalaisamy P Velavan; Olusola Ojurongbe (Public Library of Science (PLoS), 2021)
Background The risk of co-infection with Schistosoma haematobium and S. mansoni and the potential harmful effect on morbidity and control is enhanced by the overlapping distribution of both species in sub-Saharan Africa. Despite the reported high endemicity of both species in Nigeria, studies on the spread and effect of their mixed infection are limited. Therefore, a cross-sectional survey was conducted among school children in two communities in South-west Nigeria to investigate the prevalence of mixed human schistosome infection, intensity, and possible ectopic egg elimination. Methods Urine and stool samples were collected from consenting school children in Ilie and Ore communities of Osun State, Nigeria. Schistosoma haematobium eggs were detected in urine using the urine filtration technique, while S. mansoni eggs were detected in stool using the Kato-Katz thick smear technique. Results The study enrolled 466 primary and secondary school children (211; 45.3% males vs. 255; 54.7% females; mean age 11.6 ± 3.16 years). The overall prevalence of schistosomiasis was 40% (185/466), with 19% (89/466) recording single S. haematobium infection while 9% (41/465) had a single S. mansoni infection. The geometric mean egg count for S. haematobium was 189.4 egg/10ml urine; 95% CI: range 115.9-262.9, while for S. mansoni, it was 115.7 epg; 95% CI: range 78.4-152.9. The prevalence of ectopic S mansoni (S. mansoni eggs in urine) was 4.7%, while no ectopic S. haematobium (S. haematobium eggs in stool) was recorded. Mixed infection of S. haematobium/S. mansoni had a prevalence of 9.5% (44/466). More females (54.5%) presented with S. haematobium/S. mansoni co-infection. For both parasites, males had higher infection intensity, with a significant difference observed with S. haematobium (p = 0.0004). Hematuria was significant in individuals with single S. haematobium infection (p = 0.002), mixed ectopic S. haematobium/S. mansoni (p = 0.009) and mixed S. haematobium/S. mansoni/ectopic S. mansoni (p = 0.0003). Conclusions These findings suggest the probability of interspecific interactions between S. haematobium and S. mansoni. Scaling up of mass administration of praziquantel and control measures in the study areas is highly desirable.